A new polyploid species of Limonium (Plumbaginaceae) from the Western Mediterranean basin - Ferrer-Gallego, Pedro Pablo; Navarro, Albert; Pérez, Patricia; Roselló, Roberto; Rosselló, Josep; Rosato, Marcela; Laguna, Emilio (Phytotaxa, 2015)
A new species of Plumbaginaceae, Limonium irtaensis, is described and illustrated from the Western Mediterranean basin (Iberian Peninsula). The new species is triploid (2n = 26) and shows a papillate stigma and pollen with a fine reticulate exine (B type). A detailed morphological description is given, and its main diagnostic characters are compared with the related species. Conservation status has been assessed according to the IUCN protocol.